Do C1q-Positive Donor Specific Antibodies have Prognostic Effect in Patients with Resistant Antibody-Mediated Rejection Treated with Bortezomib? Single-Centre Experience. (July 2018) - Slatinska, Janka; Honsova, Eva; Rohal, Tomas; Kratochvilova, Iva; Hruba, Petra; Viklicky, Ondrej
Abstract : Introduction and Aims: Donor-specific antibodies (DSAs) examination is a crucial part of antibody-mediated rejection (AMR) diagnosis. C1q-positive (+) DSAs are associated with poor graft survival. We analyzed results of patients (pts) treated for acute resistant AMR by a bortezomib-based regimen with retrospectively performed C1q assay. The aim of this work was to analyze the treatment effect on DSA levels and potential effect of C1q+ DSAs on graft survival. Methods: We retrospectively analyzed documentation of 772 pts who underwent renal transplantation (Tx) between 1/2012-6/2015. Novel therapeutic approach to resistant acute AMR in kidney transplant recipients was applied in 23 pts (3%) based on administration of bortezomib (B) [1 cycle of 4 doses of B (1.3 mg/m2)], small doses of i.v. steroids, plasmapheresis (PP) and a dose of rituximab (375mg/m2). This protocol was administered after conventional treatment had failed. Resistant AMR was defined as persisting deterioration or non-function of renal allograft in pts with histological verification of AMR, positive C4d staining and detection of DSA receiving standard antirejection treatment with PP + IVIG. C1q assay was performed 3 times – before Tx, at the time of diagnosis and after AMR treatment. Pts were followed for minimum of 24 months. Results: Therapy of resistant acute AMR was administered to 23 pts after kidney Tx with median peak PRA 52%, actual PRA 36%, mean HLA mismatch in HLA-A 1.2 ± 0.4, HLA-B 1.7 ± 0.5, HLA-DR 1.3 ± 0, with median of 5.8 years on dialysis. 3 pts underwent 1st kidney Tx, while 20 pts reTx. All pts received induction therapy with antithymocyte globulin (n=22) or basiliximab (n=1), and maintenance immunosuppression with tacrolimus, mycophenolate mofetil/enteric-coated mycophenolate sodium and corticosteroids. Diagnosis of resistant acute AMR was made on 14th POD (7- 60 days). Using bortezomib regimen in treating resistant acute AMR led to decrease in DSA quantity in HLA especially in class I (p=0.005), class II (p = 0.015), but not in DQ (p= 0.2). No significant improvement of renal function was observed during the follow-up. The pts whose levels of serum creatinine increased more than 25% of baseline level in 6 months after administration of protocol with B, are progressors (n=11). The progressors graft survival was 57% in 2 years. The treatment protocol was not effective in decreasing C1q+ DSAs class I (p=0.25), class II (p=0.69), DQ (p=0.58). We detected C1q+ in 11 out of 11 progressors, compared with 3 out of 12 non-progressors (p<0.001). C1q+ DSAs correlated with C4d+ in graft biopsies at the time of AMR diagnosis (p=0.0012). Conclusions: Bortezomib-based regimen was effective against class I and II DSAs, but it did not affect DQ DSAs. Pts with any C1q+ DSAs were more likely to have progressive graft dysfunction compared to those with C1q-negative DSAs. C1q positivity is a promising prognostic marker in pts with resistant AMR.